An Insect-Scale Flapping-Wing Micro Aerial Vehicle Inspired by Tumblers Capable of Uncontrolled Self-Stabilizing Flying - Xiang Lu; Yulie Wu; Jie Chen; Yang Chen; Xuezhong Wu; Dingbang Xiao (Research)
As an emerging frontier in biomimetic intelligent microsystems, insect-scale flapping-wing micro aerial vehicles (FWMAVs) demonstrate significant application potential due to their exceptional maneuverability and stealth capabilities. This study proposes a novel mechanical self-stabilization architecture validated through systematic engineering design to address the critical challenge of balancing dynamic instability with payload constraints in stable flight control. By integrating a piezoelectric direct-drive actuator to streamline transmission mechanisms with the optimized V-wing configuration, we developed a V-wing FWMAV prototype weighing 204 mg (wingspan: 68 mm) that demonstrates 41.5% enhanced lift performance and 40% reduction in structural asymmetry errors compared to previous iterations. To overcome the inherent limitations of conventional control methods in payload capacity and response latency, we engineered a cylindrically symmetric damping mechanism. Through the symmetrical aerodynamic design of the top layout, this innovation generates 3-dimensional restoring moments through optimized vortex distribution patterns, achieving isotropic damping effects in the vertical axis. Experimental results reveal that the 241-mg Tumbler FWMAV equipped with this damper exhibits breakthrough stabilization performance: Vertical stabilization duration shows 5- and 20-fold improvements over conventional cross-type dampers and undamped systems, respectively, enabling stable untethered hovering flight exceeding 15 s. The established integrated design paradigm combining structural optimization, aerodynamic enhancement, and passive stabilization control provides a new way to the longstanding technical bottleneck between payload capacity and dynamic stability in insect-scale FWMAVs.